The impact of sustainability disclosure Quality on earnings quality - Khalled Muafe Khaled, Bubaker; Abbas Hasan Alharash, Mohamed; Abdelsayd Ahmida Gebril, SABRI (Dirasat in Economics and Business, 2024)
The current study examines the influence of the quality of sustainability disclosure on earnings quality using a sample of Libyan industrial companies for the period 2016-2020. In order to investigate this relationship, both quantity and quality of sustainability disclosure is measured using a multidimensional method, whereas, earnings quality is measured by adopting two approaches which are accrual-basis and real activities approach. The main results of this study show that the quality of sustainability disclosure is positively and significantly related to earnings quality suggesting that companies with high level of sustainability disclosure quality report higher level of earnings quality.